Chicoric Acid: Natural Occurrence, Chemical Synthesis, Biosynthesis, and Their Bioactive Effects - Yang, Min; Wu, Chao; Zhang, Tianxi; Shi, Lei; Li, Jian; Liang, Hongbao; Lv, Xuzhen; Jing, Fengtang; Qin, Lu; Zhao, Tianlun; Wang, Chenxi; Liu, Guangxu; et al. (Frontiers in Chemistry, 2022)
Chicoric acid (CA) has been widely used in food, medicine, animal husbandry and other different commercial products because of its significant pharmacological activities. However, the shortage of chicoric acid limits its further development and utilization. At present, Echinacea purpurea is widely used as the main natural source of chicoric acid, while other sources of it are poorly known. Extracting chicoric acid from plants is the most common approach. Meanwhile, the content of chicoric acid varies in different plants and the same plant from different producing areas and in different medicinal parts and with different extraction methods. Thus, we reviewed a comprehensive information about the sources of chicoric acid from plant extracts, chemical synthesis, biosynthesis and bioactive effects to explore an advantage path of chicoric acid for further study.